Tantangan Pendidikan Islam di Indonesia pada Era Globalisasi - Ahdar; Musyarif (Al-Ishlah: Jurnal Pendidikan Islam, 2019)
Globalization has brought about the transformation of social life in various segments. Open territoriality between countries by information and communication technology. This has implications for the dimension of life especially in the existence and projection of Islamic education. Islamic education faces multidimensional and complex challenges such as technology, ideology, social, cultural, economic and political. Other challenges are professionalism, integrity, solidarity and vision. Present and future educational solutions with increased human resources include the ability to give birth to humans who can contribute to national development; the ability to produce human beings who can appreciate, enjoy and maintain the results of development, and the ability to produce humanitarian and humanitarian processes continuously towards a nation that is just and wise. Islamic education provides an effective and efficient solution in managing the social life system in the midst of multidimensional globalization.